2015
DOI: 10.1177/0960327115579432
|View full text |Cite
|
Sign up to set email alerts
|

Can argyrophilic nucleolar organizing region-associated protein amount be used for the detection of cardiac damage?

Abstract: Introduction: Carbon monoxide (CO) is a colorless, tasteless, odorless, nonirritant gas and CO poisoning affects all organ systems. Aim: We aimed to detect any possible effects of CO exposure on the argyrophilic nucleolar organizing region (AgNOR)-associated protein synthesis of heart cells and whether there is any relationship between AgNOR protein amount and both carboxyhemoglobin (COHb) level and histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 18 publications
3
28
2
2
Order By: Relevance
“…NORs are surrounded by a great number of regulatory proteins in interphase and they are functional subunits of the nucleolus (23). We reported that the AgNOR protein amount increased depending on the increase of CO exposure (also it caused hypoxic condition) in the lung and heart cells in our previous studies (16)(17)(18). In our current study, the TAA/NA ratio and total AgNOR number per total nuclear number increased depending on the I/R injury in the tubular cells of kidney, too.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…NORs are surrounded by a great number of regulatory proteins in interphase and they are functional subunits of the nucleolus (23). We reported that the AgNOR protein amount increased depending on the increase of CO exposure (also it caused hypoxic condition) in the lung and heart cells in our previous studies (16)(17)(18). In our current study, the TAA/NA ratio and total AgNOR number per total nuclear number increased depending on the I/R injury in the tubular cells of kidney, too.…”
Section: Discussionsupporting
confidence: 64%
“…Bacause of the silver affi nity, those proteins are named argyrophilic NOR (AgNOR)-associated proteins and silver staining method is the most reliable to show nucleoli in interphase nuclei (6). A lot of studies have been carried out about the importance of AgNOR proteins such as benign and malignant thyroid tissue (7)(8)(9)(10)(11), hair root cells of humans with alopecia or healthy individuals (12,13), buccal epithelial cells of Down syndrome infants and healthy persons (14,15), the effects of CO exposure on the NOR protein synthesis of hearth and lung cells (16)(17)(18) and so on. However, to our knowledge, there are no researches in the literature about the association between AgNOR proteins and renal ischemia/reperfusion (IR) injury.…”
Section: Introductionmentioning
confidence: 99%
“… Arterial blood gas analysis-metabolic acidosis (which may occur secondary to lactic acidosis that is a result of ischemia) can be detected. (21).…”
Section: Diagnosis Of Poisoning and Detection Of The Toxicitymentioning
confidence: 99%
“…These regions can be stained with silver, when active. Depending on the silver, these proteins are called argyrophilic NOR (AgNOR) related proteins, and the silver staining method is the most suitable to indicate nucleoli in the interphase nuclei (16,17). There are several studies on the importance of interphase AgNOR quantifi cation in tumor pathology for prognostic and diagnostic defi nitions of different types of cancer (18).…”
Section: Introductionmentioning
confidence: 99%